2021
DOI: 10.1007/s00445-020-01428-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and collapse of the 2018–2019 lava dome of Merapi volcano

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…This finding is qualitative, however, especially since optical effects by hydro-meteorological conditions are commonly challenging for photogrammetric methods, but our drone analysis provides nevertheless a first-order estimate on the increase of sulfuric deposition and acid sulfate alteration. The area of the southern sector was covered by renewed dome lava extrusion in 2018, but subsequently collapsed and is now the site of frequent mass wasting events and the origin of pyroclastic density currents during the recent (post 2019) crisis of Merapi volcano 10 , 26 , 42 (see also below).
Figure 3 Temporal changes at Merapi summit dome.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is qualitative, however, especially since optical effects by hydro-meteorological conditions are commonly challenging for photogrammetric methods, but our drone analysis provides nevertheless a first-order estimate on the increase of sulfuric deposition and acid sulfate alteration. The area of the southern sector was covered by renewed dome lava extrusion in 2018, but subsequently collapsed and is now the site of frequent mass wasting events and the origin of pyroclastic density currents during the recent (post 2019) crisis of Merapi volcano 10 , 26 , 42 (see also below).
Figure 3 Temporal changes at Merapi summit dome.
…”
Section: Resultsmentioning
confidence: 99%
“…3 ) and then partially collapsed producing a hazardous pyroclastic density current in 2019 (Refs. 10 , 26 , 42 ). Moreover, this area is also the site of frequent mass wasting events, and thus the origin of pyroclastic density currents, during the most recent (post 2019) crisis at Merapi volcano.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of such growth and collapse, however, may be strongly dependent on the local site conditions. At Merapi, it was recently identified that the mechanism of collapse is controlled by the basement and dome slopes, which also control the directions of destruction episodes (Kelfoun et al, 2021). At Shiveluch, when considering the outlines and directions of the western (originating in 2005) and eastern (originating in 2010) collapse scars, we find that these azimuthal directions have a certain longevity.…”
Section: Conceptual Model For the 2018-2019 Constructive And Destructive Eventsmentioning
confidence: 61%
“…The complex interrelation and even bidirectional interaction of events responsible for constructing and destroying the volcano edifice have been identified for volcanoes worldwide, both on land (Germa et al, 2015) and in the ocean (Sibrant et al, 2014). The relevant observations range from local-scale lava dome growth and collapse (Kelfoun et al, 2021) to large-scale ocean islands, where collapse-related unloading even affects deep crustal magma reservoirs (Manconi et al, 2009). The details of such growth and collapse, however, may be strongly dependent on the local site conditions.…”
Section: Conceptual Model For the 2018-2019 Constructive And Destructive Eventsmentioning
confidence: 99%